Corrole-gold nanoparticles: Synthesis, ground and excited state solvation. (May 2022) - Barata, Joana F.B.; Serra, Vanda Vaz; Daniel-da-Silva, Ana L.; Neves, M. Graça P.M. S.; Costa, Sílvia M.B.; Cavaleiro, José A.S.; Trindade, Tito
Abstract: The in situ preparation and the full spectroscopic characterization of corrole - gold nanoparticles (AuTPFCS) are reported. The synthetic approach to these nanoconjugates involved the reaction of a mercaptocorrole (TPFCSH) with chloroauric acid under reductive conditions. Fluorescence quantum yields and time resolved lifetimes showed a significant quenching of the mercaptocorrole after its covalent coupling to the gold nanoparticles in acetonitrile and in toluene. Irradiated samples of AuTPFCS with a Nd:YAG laser in toluene solution revealed the distribution of larger nanoparticles from 3.1 to 11 nm viewed by TEM images. Graphical abstract: The in situ synthesis and ground and excited state of corrole-gold nanoparticles (AuTPFCS) are reported. Image 1